Stephen King - Stefoff, Rebecca, 1951- (New York : Marshall Cavendish Benchmark, 2011)
Describes the life and works of Stephen King, a well-known writer of horror novels and stories, discussing his childhood with strong mother and an absent father, his writing style, film and television adaptations of King's works, and the controversy surrounding the violent and graphic subject matter that appears in King's writing.
Includes bibliographical references (p. 154-169), filmography (p. 147-149), and index.
Young Adult.
Young Adult
Keywords: King, Stephen, -- 1947- -- Juvenile literature; King, Stephen, -- 1947-; King, Stephen, -- 1947-; Horror tales -- Authorship -- Juvenile literature; Novelists, American -- 20th century -- Biography -- Juvenile literature; Novelists, American; American novelists -- Biography